1998
DOI: 10.1016/s1368-8375(98)00047-5
|View full text |Cite
|
Sign up to set email alerts
|

The Swedish Snus and the Sudanese Toombak: are they different?

Abstract: In Sweden, snu (locally known as snus), was introduced since the year 1637. Presently, Sweden has the highest per capita consumption and sale ®gures of snu in the world, and the habit is becoming increasingly popular. Snus is manufactured into a dry form used in the nasal cavity and a moist form used in the oral cavity. Snus manufactured for oral use is a moist ground tobacco of Dark Kentucky or Virginia species mixed with an aqueous solution of water and other blending ingredients. This form of snu is found i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
122
1
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(130 citation statements)
references
References 32 publications
2
122
1
5
Order By: Relevance
“…Approximately 23% of Swedish men are reported to use snus (Foulds 2003). In Sudan, about 40% of males and 10% of females use toombak (local name of ST) (Idris et al, 1996;Idris et al, 1998). Today, the trade of certain types of ST, such as moist snuff, is also illegal in several countries, e.g., in Saudi Arabia, Japan, Hong Kong, Singapore, Australia and New Zealand (Klus et al, 2009).…”
Section: Smokeless Tobacco (Shammah) In Saudi Arabia: a Review Of Itsmentioning
confidence: 99%
“…Approximately 23% of Swedish men are reported to use snus (Foulds 2003). In Sudan, about 40% of males and 10% of females use toombak (local name of ST) (Idris et al, 1996;Idris et al, 1998). Today, the trade of certain types of ST, such as moist snuff, is also illegal in several countries, e.g., in Saudi Arabia, Japan, Hong Kong, Singapore, Australia and New Zealand (Klus et al, 2009).…”
Section: Smokeless Tobacco (Shammah) In Saudi Arabia: a Review Of Itsmentioning
confidence: 99%
“…A number of studies have characterized smokeless tobacco as an etiological factor in the development of cancer of the oral cavity 31,32 and the esophagus. One study from Sweden showed that snus dipping (snuff dipping) increased the risk of oral cancer by 5-to 6-fold 33 . As said before OSMF has a malignant transformation rate of 7-30%.…”
Section: Early Symptomsmentioning
confidence: 99%
“…Some of the ingredients are tar, carbon monoxide, nicotine and other chemicals and additives such as ammonia, arsenic (a poison used in insecticides and weed killers), benzene, hydrogen cyanide and many others. Millions of pregnant women use smokeless tobacco, predominantly in Africa and Asia [14] but also in Scandinavia [15]. These women are not exposed to the combustion products in tobacco smoke (e.g.…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%
“…The baby also might be considerably light in weight. If certain genetic susceptibilities are present, the harmful effects of smoking during pregnancy are multiplied [40,41,42].…”
mentioning
confidence: 99%